Rejoiner: The long road to publishing: A friendly expose - De Lange, Paul (Routledge, 2005)
My insight into the long road to publishing has produced six enlightened Commentaries, which I believe promote greater understanding for all interested readers. I should like to commence my Rejoinder by thanking those individuals who made time to comment on my paper. The purpose of my Rejoinder, according to the invitation from the Editor of Accounting Education (Richard M. S. Wilson) is to stimulate further debate on the original theme in my paper. To achieve this objective I shall address each Commentary in turn, with a view to consolidating commonalities, justification for departures and to provide new insights.